Activity of an anaerobic Thermoanaerobacterales hydrolase on aliphatic and aromatic polyesters - Siracusa, Chiara; Fohler, Lisa; Leibetseder, Lukas; Striedner, Gerald; Oostenbrink, Chris; Quartinello, Felice; Guebitz, Georg M.; Ribitsch, Doris (Frontiers in Bioengineering and Biotechnology, 2025)
This study focuses on the biochemical characterization of a new hydrolase (Thb) expressed from anaerobic Thermoanaerobacterales, which could be used to improve biogas plant efficiency for plastic waste treatment. The specificity of Thb for various polyesters, including polyethylene terephthalate (PET), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), and polylactic acid (PLA), was compared to the well-studied cutinase HiC from Humicola insolens. Based on gravimetric analysis and quantification (high-performance liquid chromatography (HPLC)) of monomers solubilized upon enzymatic hydrolysis, Thb was found to be more active on aromatic polyesters, while HiC led to a higher amount of hydrolysis products on aliphatic polyesters (PBS and PLA). Polyester hydrolysis was further investigated by scanning electron microscopy and infrared spectroscopy. A comparison of the two enzyme structures indicated the higher aromatic character of specific regions of the Thb surface as a possible reason for these differences in specificity.